“The rituals I do are firm!” - the Queen’s gesture - Anjos, Jean Souza dos (GIS - Gesture, Image and Sound - Anthropology Journal, 2021)
Photo essay on the rituals of Rainha Pombagira Sete Encruzilhadas in the Cabana do Preto Velho da Mata Escura, in Fortaleza-CE. A work, a macumbeira anthropology that moves and bewitches. The enchanted images reveal what you can look at and keep the sacred secrets, gestures. The visible and the invisible find themselves revealing poetics, interstices and knowledge.